Spatial analysis and specific nutrition intervention factors associated with the prevalence of stunting in Aceh Province, 2022 - Azhari Azhari; Muhammad Yani; Herlina Dimiati; Nurjannah Nurjannah (AcTion: Aceh Nutrition Journal, 2025)
Aceh is an Indonesian province with a persistently high prevalence of stunting. Spatial analysis of the prevalence of stunting and the performance of specific nutrition interventions provides essential evidence for identifying priority areas for action. Mapping intervention coverage enables local governments to determine strategic measures tailored to district needs. This study aimed to map and analyze the relationship between stunting prevalence and the coverage of specific nutrition interventions, including (1) supplementary feeding for pregnant women, (2) iron–folic acid supplementation for pregnant women, (3) iron supplementation for adolescent girls, (4) exclusive breastfeeding, (5) supplementary feeding for underweight children, (6) growth monitoring, and (7) basic immunization. A cross-sectional design was applied to 23 districts/cities in Aceh. Secondary data were obtained from the 2022 Indonesian Nutrition Status Survey (INSS) and Aceh Provincial Health Office profile. Spatial mapping was conducted using overlay techniques, followed by linear regression analysis to assess the association between intervention coverage and district-level stunting prevalence. Supplementary feeding of pregnant women was significantly associated with stunting prevalence (p= 0.040). No significant associations were observed for iron folic acid supplementation in pregnant women (p= 0.961), iron supplementation in adolescent girls (p= 0.066), exclusive breastfeeding (p= 0.559), supplementary feeding for underweight children (p= 0.347), growth monitoring (p= 0.318), or basic immunization (p= 0.219). In conclusion, supplementary feeding for pregnant women is significantly associated with stunting prevalence, underscoring its critical role in specific nutritional interventions and its relevance in developing targeted regional policies